Imam Bukhari's Contributions To The Development Of Islamic Science - Jumayeva Shaxlo Suyunovna (Global Scientific Publishing, 2025)
The present article explores the remarkable role of Imam Muhammad ibn Ismail al-Bukhari in the development of Islamic sciences, especially in the areas of hadith methodology and authentication. The results indicate that Bukhari's efforts not only protected the prophetic traditions but also laid down a scholarly framework that merged historical criticism, jurisprudence, and ethics, thereby giving a significant push to the overall development of the Islamic intellectual tradition.
Keywords: Imam Bukhari; hadith science; Islamic scholarship